Evaluation of potential geothermal resource areas - Mitchell, Franklin O. (Johns Hopkins University. Applied Physics Laboratory, 1979)
A method for the comparative evaluation of geothermal prospects in the Eastern United States is proposed and illustrated. Comparisons are based on quantified data from geologic, engineering, and socio-economic sources including temperature gradient, depth to basement, drilling costs, population, and distribution by town size, as well as energy use in residential, commercial, and industrial applications.